Correction: Al Khatib et al. Inhaled Medicines for Targeting Non-Small Cell Lung Cancer. Pharmaceutics 2024, 15, 2777 - Arwa Omar Al Khatib; Mohamed El-Tanani; Hisham Al-Obaidi (MDPI AG, 2024)
In the original publication [...]